Resource utilization of an LGBT university resource center and prospective barriers - Sokolowski, Elizabeth, author; Chavez, Ernest, advisor; Rickard, Kathryn, committee member; Carlson, Laurie, committee member (Colorado State University. Libraries, 2018)
The microclimate of an LGBT resource center was examined for its overall use of services and potential barriers to use. The responses of 38 LGBT students in 2011 and 30 LGBT students in 2015, all from one university, were examined to determine if the overall use of services provided by the LGBT resource center changed across time and whether overall awareness of services, the microclimate atmosphere at the resource center, and the name of the resource center acted as barriers to use. Overall use of services significantly decreased from 2011 to 2015, and awareness was the only significant barrier related to overall use of services. An analysis of the relationship of identities (e.g., sex, gender, sexual orientation, and ethnicity) to overall use and the barriers to use found that sex and sexual orientation were significantly related to perception of microclimate atmosphere within the resource center.